S‐Adenosylmethionine‐mediated apoptosis is potentiated by autophagy inhibition induced by chloroquine in human breast cancer cells. Issue 2 (22nd June 2017) - Cave, Donatella Delle; Desiderio, Vincenzo; Mosca, Laura; Ilisso, Concetta P.; Mele, Luigi; Caraglia, Michele; Cacciapuoti, Giovanna; Porcelli, Marina
Abstract : The naturally occurring sulfonium compound S‐adenosyl‐L‐methionine (AdoMet) is an ubiquitous sulfur‐nucleoside that represents the main methyl donor in numerous methylation reactions. In recent years, it has been shown that AdoMet possesses antiproliferative properties in various cancer cells, but the molecular mechanisms at the basis of the effect induced by AdoMet have been only in part investigated. In the present study, we found that AdoMet strongly inhibited the proliferation of breast cancer cells MCF‐7 by inducing both autophagy and apoptosis. AdoMet consistently enhanced the levels of the autophagy markers beclin‐1 and LC3B‐II, and caused a significant increase of pro‐apoptotic Bax/Bcl‐2 ratio paralleled by poly (ADP ribose) polymerase (PARP) and caspase 9, and 6 cleavage. Notably, AdoMet, already at low doses, raised the percentage of cells in G2 /M phase of cell cycle by down‐regulating the expression of cell cycle‐regulatory proteins cyclin B and cyclin E with a remarkable increase of p53, p27, and p21. We also evaluated the combination of AdoMet and the autophagy inhibitor chloroquine (CLC) showing that autophagy block is synergistic in inducing both growth inhibition and apoptosis. These effects were paralleled by a strong inhibition of the activity of AKT and of the downstream effector mTOR and by an increased cleavage of caspase‐6 and PARP. These data suggest, for the first time, that autophagy can act as an escape mechanism from the apoptotic activity of AdoMet, and that AdoMet could be used in combination with CLC or its analogs in the treatment of breast cancer. Abstract : AdoMet induces apoptosis in breast cancer cells through the inhibition of Akt. Autophagy is also activated and is a mechanism of escape from apoptosis induced by AdoMet. Cloroquine and AdoMet combination strongly potentiates the apoptosis induced by AdoMet blocking autophagy occurrence.